Pengaruh Pengambilan Keputusan dan Pengambilan Resiko Terhadap Kinerja Usaha Franchise di Kota Makassar: The Role Moderating Of Financial Technology (Studi Pada Perusahaan Franchise BExpress Fried Chicken) - Rosmini, Sri Wahyuningsi; Raprayogha, Rusdi; Farild, Miftha (Universitas Islam Negeri Alauddin Makassar, Indonesia, 2024)
This research aims to determine the influence of decision making and risk taking on the performance of franchise businesses in Makassar City: the moderating role of financial technology. This research uses primary data, the sampling technique in this research is purposive sampling technique using the Slovin formula, so the total sample in this research is 70 respondents. In this research, Structural Equation Modeling (SEM) was used using SmartPLS version 4.0 for Windows as a data analysis technique. The results of the research show that decision making has no direct effect on BExpress Fried Chicken Franchise business performance, risk taking has a significant positive effect on BExpress Fried Chicken Franchise business performance, decision making has a direct effect on Franchise business performance in Makassar City: through The Role Moderating of Financial Technology, and Risk taking has a direct effect on franchise business performance in Makassar City: through The Role Moderating of Financial Technology. Keywords: Decision Making, Risk Taking, Business Performance and Financial Technology.